Phase transitions in Ca2−xBaxNdSbO6 complex perovskites: a combined crystallographic and vibrational investigation. Issue 22 (22nd May 2019) - Halder, Saswata; Sinha, T. P.
Abstract : Phase transitions in Ca2− x Ba x NdSbO6 complex perovskites resulting from altered Ca/Ba compositions swap the local conformational environment of Nd 3+ . Abstract : An investigation into crystal structures and vibrational degrees of freedom depending on a compositionally altered A-site chemistry is performed for complex perovskites Ca2− x Ba x NdSbO6 (0 ≤ x ≤ 2) in order to study the sequence of phase transitions and changes in the local coordination environment. X-ray crystallographic investigations show that the samples 'toggle' between the pure states of monoclinic Ca2 NdSbO6 (CNS) and rhombohedral Ba2 NdSbO6 (BNS) with changes in composition. A novel observation is made from the crystallographic results which display crystallographic site swapping of the Nd 3+ ion when the structure transforms from CNS to BNS. The degree of this conformational site swapping of the Nd 3+ ion has been correlated to the Ca/Ba size ratio at the A site of the perovskite lattice. The Raman spectra of the series Ca2− x Ba x NdSbO6 show remarkable signatures of a discontinuous monoclinic–rhombohedral phase transformation. A high temperature Raman analysis is carried out between 303 K and 673 K to explain the presence of a nearby rhombohedral ( R 3̄)-cubic ( Fm 3̄ m ) phase boundary. The thermal variations of the Raman spectra show a quasi-harmonic nature owing to the presence of weak rhombohedral distortion which is not effective in activating a change in the Raman profile.